Igneous mineralogy at Bradbury Rise: The first ChemCam campaign at Gale crater. Issue 1 (8th January 2014) - Sautter, V.; Fabre, C.; Forni, O.; Toplis, M. J.; Cousin, A.; Ollila, A. M.; Meslin, P. Y.; Maurice, S.; Wiens, R. C.; Baratoux, D.; Mangold, N.; Le Mouélic, S.; et al.
Abstract [1] Textural and compositional analyses using Chemistry Camera (ChemCam) remote microimager and laser‐induced breakdown spectroscopy (LIBS) have been performed on five float rocks and coarse gravels along the first 100 m of the Curiosity traverse at Bradbury Rise. ChemCam, the first LIBS instrument sent to another planet, offers the opportunity to assess mineralogic diversity at grain‐size scales ( 100 µm) and, from this, lithologic diversity. Depth profiling indicates that targets are relatively free of surface coatings. One type of igneous rock is volcanic and includes both aphanitic (Coronation) and porphyritic (Mara) samples. The porphyritic sample shows dark grains that are likely pyroxene megacrysts in a fine‐grained mesostasis containing andesine needles. Both types have magnesium‐poor basaltic compositions and in this respect are similar to the evolved Jake Matijevic rock analyzed further along the Curiosity traverse both with Alpha‐Particle X‐ray Spectrometer and ChemCam instruments. The second rock type encountered is a coarse‐grained intrusive rock (Thor Lake) showing equigranular texture with millimeter size crystals of feldspars and Fe‐Ti oxides. Such a rock is not unique at Gale as the surrounding coarse gravels (such as Beaulieu) and the conglomerate Link are dominated by feldspathic (andesine‐bytownite) clasts. Finally, alkali feldspar compositions associated with a silica polymorph have been analyzed in fractured filling material of Preble rock and in Stark, a putative pumice or an impact melt. These observations document magmatic diversity at Gale and describe the first fragments of feldspar‐rich lithologies (possibly an anorthosite) that may be ancient crust transported from the crater rim and now forming float rocks, coarse gravel, or conglomerate clasts.